2019
DOI: 10.1002/gps.5166
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and suicide risk in older adults: A retrospective longitudinal cohort study

Abstract: Objectives The present study evaluated suicide risk within 1 year after discharge among older adults with stroke as a function of depression onset. Method We used the Korean National Health Insurance Service‐Senior cohort data and included first discharged patients with a stroke as the principal diagnosis. The comparison group was selected by a 1:2 case‐control propensity score matching for age, sex, Charlson comorbidity index, and diagnosis year between 2005 and 2012. Suicide deaths were measured by code for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…People were divided into categories of young-old (age 60-74 years) and oldold (age > 75 years) based on a previous study. 41,42 The year of the first diagnosis of dementia in the study period was defined as the index year, and the members of the comparison group were matched with patients with dementia in the same index year. The comorbidities were diabetes mellitus (ICD-10 codes E10-E14), hypertension (ICD-10 codes I10-I15), dyslipidemia (ICD-10 code E78), Parkinson disease (ICD-10 code G20), stroke (ICD-10 codes I60-I63), ischemic heart disease (ICD-10 codes I20-25), chronic kidney disease (ICD-10 code N18) and cancer (ICD-10 codes C00-C99) and were estimated by screening information from medical records before the index date.…”
Section: Data and Study Samplementioning
confidence: 99%
“…People were divided into categories of young-old (age 60-74 years) and oldold (age > 75 years) based on a previous study. 41,42 The year of the first diagnosis of dementia in the study period was defined as the index year, and the members of the comparison group were matched with patients with dementia in the same index year. The comorbidities were diabetes mellitus (ICD-10 codes E10-E14), hypertension (ICD-10 codes I10-I15), dyslipidemia (ICD-10 code E78), Parkinson disease (ICD-10 code G20), stroke (ICD-10 codes I60-I63), ischemic heart disease (ICD-10 codes I20-25), chronic kidney disease (ICD-10 code N18) and cancer (ICD-10 codes C00-C99) and were estimated by screening information from medical records before the index date.…”
Section: Data and Study Samplementioning
confidence: 99%
“…It has been found that lower SES could lead to a higher risk of mental health problems. For example, a cohort study analyzing the National Health Insurance Service-Senior claims data in Korea found that the poverty group had a higher risk of suicide than the high-income group among Korean adults aged 60 to 74 years old [ 20 ]. On the other hands, we should be cautious about interpreting the statistically non-significant results in the mediation analysis about education attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Like preceding health outbreaks such as the 2002 severe acute respiratory syndrome, the present COVID-19 appears to be leading to higher suicidality (Griffith & Mamum, 2020). Aside of COVID-19, approximately 75% of suicides occur in low and middle-income countries (LMICs) where rates of poverty are high [macrocosms], and evidence proposes a relationship between economic variables and suicidal behavior [microcosms] (Bantjes et al, 2016:1;Choi, Kim, Shin, & Han, 2019). In this COVID-19 pandemic, most of the suicides occur due to lockdown-related economic recession (Bhuiyan, Sakib, Pakpour, Griffiths, & Mamum, 2020;Mamun & Ullah, 2020).…”
Section: Suicidal Ideation and Suicides Related To Covid-19 Pandemicmentioning
confidence: 99%